Development of Educational Video Capsules for Active Learning in Environmental Sciences through Universal Design for Learning - Navarro, Nuria; Corrales, Patricia; Vila-Bedmar, Rocio; González-Montesino, Rayco H.; de Luis, Oscar; Espada-Chavarria, Rosa (Education sciences, 2024)
Social changes in higher education have led to a transformation in teaching innovation for developing a critical and creative mentality in students. To this end, video capsules have emerged as an optimal tool that allows combining the management of information and communication technologies and collaborative work. Video capsules were elaborated by groups of students for the virtualization of the laboratory practices of the subjects Environmental Microbiology and Biochemistry of the Degree in Environmental Sciences for two academic years (2022–2023 and 2023–2024), paying special attention to the principles of Universal Design of Learning. To assess the impact of this activity on the knowledge acquired by the students in the laboratory practices, the marks from these academic years were compared with the previous academic year (2021–2022) without the generation of video capsules. Moreover, an evaluation of the development and acquisition of cross-curricular competencies was carried out. The generation of video capsules by the students tended to increase the average grade obtained in the laboratory practices of both subjects. Furthermore, instrumental, interpersonal, and systemic competencies obtained by the students by performing the video capsules improved their transversal skills. The creation of video capsules during laboratory practices and the methodology used had a very positive direct influence on the academic outcomes of the subjects and facilitated the acquisition of transversal competencies for the students.